Effects of classrooms’ architecture on academic performance in view of telic versus paratelic motivation: a review - Lewinski, Peter (Frontiers in Psychology, 2015)
This mini literature review analyzes research papers from many countries that directly or indirectly test how classrooms’ architecture influences academic performance. These papers evaluate and explain specific characteristics of classrooms, with an emphasis on how they affect learning processes and learning outcomes. Factors such as acoustics, light, color, temperature, and seat arrangement are scrutinized to determine whether and by how much they improve or hinder students’ academic performance in classrooms. Apter’s reversal theory of telic versus paratelic motivation (1982, 1984, 2014) is presented and used to explain these findings. The results show preference for a learning environment that cues a telic motivation state in the students. Therefore, classroom features should not be distracting or arousing. Moreover, it appears the most influential factors affecting the learning process are noise, temperature and seat arrangement. In addition, there is no current agreement on how some particular physical characteristics of classrooms affect learning outcomes. More research is needed to establish stronger conclusions and recommendations.